Optimization of a Healthy Learning Environment through Waste Management and Greening Programs in the Madrasah Area - Nuniek Nizmah Fajriyah; Herni Rejeki; Firman Faradisi; Adi Sulistyo; Husna Nur Afdila; Nabila Nabila (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Optimal environmental conditions and domestic waste accumulation at MI Pakumbulan, Pekalongan, have hindered a conducive learning atmosphere. Additionally, insufficient water infiltration areas cause puddles during the rainy season, requiring integrated intervention. This community service activity aimed to optimize a healthy learning environment through waste management education, reforestation, and biopore infiltration holes. The program was implemented in three stages: socialization of 3R (Reuse, Reduce, Recycle) principles, practical planting of ornamental and productive flora, and technical training for installing biopores in flood-prone areas. Results indicated a significant increase in ecological awareness, established through an independent waste sorting system and expanded green spaces. The installation of 10 biopore points effectively improved groundwater absorption and provided organic composting sites. Both students and teachers demonstrated enhanced skills in plant care and productive waste management. This program successfully transformed the madrasah into a greener, healthier, and more educational environment. It is recommended that the school forms a